Analysis of teachers' task and extra-role performance under different autonomy regimes. Issue 4 (13th April 2015) - Duyar, Ibrahim; Ras, Nancy; Pearson, Carolyn L.
Abstract : Purpose: – Teachers constitute one of the largest groups of knowledge workers. The purpose of this paper is to examine the antecedents and outcomes of teachers' task and extra-role performance (ERP) under two different autonomy regimes in charter and regular public schools. A special emphasis was given to the ERP of teachers. Both the predictors and outcomes of teacher work performance were comparatively investigated in these two different school environments. Design/methodology/approach: – By applying a social-cognitive perspective and a causal comparative design, the study comparatively tested the reciprocal relationships among the study variables in public and charter schools. The clustered sample included 812 public school teachers and 112 charter school teachers. Findings: – The findings revealed that the predictors and outcomes of teachers' task and ERP have differing dynamics in these two distinct types of public schools. The School Type, which represented the differences in school autonomy between public and charter schools, appeared to be the strongest differentiating factor across two groups of schooling. Both types of teacher performance (task and extra role) in charter schools outweighed their counterparts in public schools. Similarities and differences were observed on the predictors and outcomes of teacher work performance. Originality/value: – The current study contributed to the scant literature on the effects of school autonomy on teacher task and ERP. A clear understanding on the predictors and outcomes of teacher work performance under two different school autonomy regimes may guide practitioners and policymakers in their efforts to bring public schools to a more competitive edge.